Comparison of Different algorithm for Speed Control of Brushless D.C Motor Using Matlab Simulink (International Journal of Scientific Research and Management (IJSRM), 2015)
Brushless DC Motors have a permanent magnet rotor and the stator winding are wound such that the back electromotive force (EMF) is trapezoidal. The motor posses high Torque/weight ratio, operate at very high speed, very compact & electronically controlled. In this paper, we have to use three algorithms ZN, GA & PSO respectively. On the basis of performance of these three techniques, PSO have high efficiency as compare to other two techniques Error rate in PSO algorithm is 1.395 which is less than ZN algorithm & GA algorithm.